2022
DOI: 10.36728/afp.v22i2.2036
|View full text |Cite
|
Sign up to set email alerts
|

The Differences Effect between Pond Types and Maggot Allotments on The Protein and Fat of Tilapia Meat

Abstract: Tilapia was one of the freshwater fish commodities that were widely consumed, so the demand for tilapia increased and impacted the high price of tilapia feed. Therefore, maggots can be used as additional fish feed, and recently there have been many variations of pond types in tilapia farming. This study aimed to determine the interaction between pond types and maggot allotments for protein and fat in tilapia meat. This study used two types of pools: tarpaulin and drum. The subjects used in this study were tila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Based on the results of this study showed that red ginger and brotowali extract did not effect to cholesterol levels. This result is in line with research by (Sulistyoningsih et al, 2018) which stated that the administration of herbal ingredients had no significant effect on broiler blood cholesterol levels. Ginger powder and cinnamon flour 1.0%, 0.2%, and 0.3%.in feed has not been able to reduce cholesterol levels (Gaiwad et al, 2020).…”
Section: Carcass Qualitysupporting
confidence: 91%
“…Based on the results of this study showed that red ginger and brotowali extract did not effect to cholesterol levels. This result is in line with research by (Sulistyoningsih et al, 2018) which stated that the administration of herbal ingredients had no significant effect on broiler blood cholesterol levels. Ginger powder and cinnamon flour 1.0%, 0.2%, and 0.3%.in feed has not been able to reduce cholesterol levels (Gaiwad et al, 2020).…”
Section: Carcass Qualitysupporting
confidence: 91%
“…However, the R1 treatment with rations containing 15% CP and ME 2750 kcal/kg was significantly smaller (P<0.05) than all treatments because the enzymes produced by microbes in the 5% FCW ration have not been able to optimize the degradation of organic matter in the digestive tract so that nutrient absorption is not optimal. Based on [41], the addition of fish waste silage at the levels of 2.5%, 5%, and 7.5% does not affect the protein content of meat (P>0.05).…”
Section: Nitrogen Retention Of Super Native Chickens Rationed With Fcwmentioning
confidence: 95%
“…According to [40], the use of shrimp shell fermentation with microbes Bacillus licheniformis, Lactobacillus sp., and Saccharomyces cerevisiae at a level of 10-15% can support the growth phase in Sentul chickens. In addition, research [41] also recommends adding fish waste silage with a concentration of 10% of the total feed given, which can improve performance in intensive maintenance and save production costs in broiler chicken feed.…”
Section: Apparent Metabolizable Energy Rations Contain Fcwmentioning
confidence: 99%
See 2 more Smart Citations